Implementation of Culturally Responsive Teaching-Based Problem-Based Learning on Students’ Analytical Thinking Skills in the Digestive System Topic in Grade XI at SMAIT Nur Hidayah - Ni'matun Nurlaili; Dwi Setyo Astuti (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to examine the effectiveness of a Problem-Based Learning (PBL) model integrated with Culturally Responsive Teaching (CRT) in enhancing students’ analytical thinking skills in learning the digestive system. A quantitative approach was employed using a quasi-experimental research design. Specifically, the study adopted a non-equivalent control group design with purposive sampling, involving 28 students in the experimental class and 28 students in the control class. Data were collected through pretest and posttest assessments and were analyzed using an independent samples t-test. The results showed that the mean posttest score of the experimental class (84.82) was higher than that of the control class (71.43), with a significance value of p < 0.001, indicating a statistically significant difference between the two groups. These findings suggest that the integration of Problem-Based Learning (PBL) and Culturally Responsive Teaching (CRT) is effective in improving students’ analytical thinking skills through culturally contextualized learning. This study contributes to the development of biology instruction grounded in local contexts, an area that remains relatively underexplored.